Breast irradiation causes pallor in the nipple‐areolar complex in women with Celtic skin type (result from the St. George and Wollongong randomised breast boost trial). Issue 2 (24th January 2014) - Lee, Yoo Young (Dominique); Hau, Eric; Browne, Lois H; Chin, Yaw; Lee, Jessica; Szwajcer, Alison; Cail, Stacy; Nolan, David N; Graham, Peter H
Abstract Introduction The nipple‐areolar complex (NAC) has special histological properties with higher melanocyte concentration than breast skin. To date, there are no data describing the late effects on the NAC following breast‐conserving therapy (BCT). This study evaluated colour changes in the NAC in patients treated with breast‐conserving surgery and adjuvant radiotherapy after 5 years. Methods Digital photographs obtained at 5 years following breast irradiation from the St. George and Wollongong (SGW) trial (NCT00138814) were evaluated by five experts using an iPad® (Apple Inc., Cupertino, CA, USA) application specifically created for this study. The SGW trial randomised 688 patients with Tis‐2, N0‐1, M0 carcinoma to the control arm of 50 Gy in 25 fractions and boost arm of 45 Gy in 25 fractions and 16 Gy in 8 fractions electron boost. Results A total of 141/372 (38%) patients had altered NAC (86% lighter, 10% darker). Patients with Celtic skin type had increased likelihood of having an altered NAC (odds ratio (OR), 1.75 (CI 1.1–2.7, P = 0.011)). On subgroup analysis, those with Celtic skin type receiving biologically equivalent dose (BED) Gy3 ≥ 80 Gy had OR of 3.03 (95% CI 1.2–7.5, P = 0.016) for having altered colour. There was a dose response with more profound changes seen in the NAC compared with irradiated breast skin if BED Gy3 ≥ 80 Gy with OR of 2.42 (95% CI 1.1–5.6, P = 0.036). Conclusion In this Caucasian BCT population, over 30% of patients developed lighter NAC and more commonly in women with Celtic skin type. The degree of this effect increased with higher radiation dose.